Fragile Spaces Forays into Jewish Memory, European History and Complex Identities (Volume 8) - Aschheim, Steven E. (De Gruyter, 2018)
This book consists of a range of essays covering the complex crises, tensions and dilemmas but also the positive potential in the meeting of Jews with Western culture. In numerous contexts and through the work of fascinating individuals and thinkers, the work examines some of the consequences of political, cultural and personal rupture, as well as the manifold ways in which various Jewish intellectuals, politicians (and occasionally spies!) sought to respond to these ruptures and carve out new, sometimes profound, sometimes fanciful, options of thought and action. It also delves critically into the attacks on liberal and Enlightenment humanism. In almost all the essays the fragility of things is palpably present and the book touches on some of the ironies, problematics and functions of responses to that condition. The work mirrors the author's ongoing fascination with the always fraught, fragile and creatively fecund confrontation of Jews (and others) with European modernity, its history, politics, culture and self-definition. In a time of increasing anxiety and feelings of fragility, this work may be helpful in understanding how people at an earlier (and sometimes contemporary) period sought to come to terms with a similar predicament.